THE IMPLEMENTATION OF GROUP INVESTIGATION IN TEACHING READING (A Quasi-Experimental Research at SMAN 24 Bandung) - pratiwi rahayu (Universitas Bunda Mulia, 2021)
ABSTRACT This study aims to find out the effectiveness of Group Investigation method in improving students’ reading ability. This quasi-experimental research design was involved 64 students of SMAN 24 Bandung as the participants. This study used a type of data collection technique including pre test and post test. The conceptual framework for the study included the independent variable of teaching method, and dependent variable of students’ ability in reading. The experimental study was conducted within this framework by using non parametric test. The results of data analysis show that Group Investigation could facilitate the students in improving their reading ability. It can be seen from the result of mean rank and Mann-Whitney U. Furthermore, the results of the pre test and post test indicate that students’ reading ability improved in four indicators, encompassing identifying the explicit information, identifying the main idea of the text, identifying the purpose of the text, and identifying the implicit information of the text. Meanwhile, the results of test in control group indicate that the students’ reading ability improved in two indicators, encompassing identifying the purpose of the text and identifying the synonym of the words. Due to the limitations of the study, it is recommended for other researchers to introduce Group Investigation gradually into the classroom and practice it before the class undertakes a full-scale investigation project and to observe the students’ social interaction skill in the classroom. It is also recommended for every teacher who wants to use this method to fully competent at implementing this method. Despite the need for the further research, this method can be used as a method in teaching reading to EFL learners.Keywords: reading ability, Group Investigation.